Birth of Olympic flame: Ancient Greece and European identity (II) - Malešević Miroslava (Glasnik Etnografskog Instituta SANU, 2010)
The anti-Chinese protests that were organized throughout European cities following the route of the Olympic torch from Athens to Beijing, and the conflicts that erupted with strong emotions on both sides between the protestors and the Chinese citizens, will without a doubt remain a lasting memory of the 2008 Olympic games. Regardless of these protests' justified motives, there is a visible paradoxical role-switch in the scenes that circled the globe for months: the Olympic torch and Olympic idea, were being defended by China as a highest value and the source of their own past and identity, and attacked by the people (Europeans) on whose land that very idea had been created and nurtured for over a hundred years. How should these contradictory images be understood? How did it come to this that the Chinese view themselves as the keepers of the Olympic tradition, that the pride of the Chinese nation, focused in that flame, gets hurt in attempts of European protestors to put it out? The modern Olympic Games, founded in 1896, were one of the echoes of a centuries' long Western European fascination with the Antique. This phenomenon of the Antique admiration has brought about a redefining of the European civilization's past, the abandoning the biblical narrative and the gradual creation of a secular story that we call modern history, in which Greece and Rome have become the main references of origin. The same process influenced the formation of national states that perceive, apart from their own histories, a collective cultural origin in Ancient Greece. Of course, the Galls, Francs or Germans had little in common with ancient Greeks; but modern European nations unite this fictional image of the Antique with the firm belief that it is the source of their cultural identity. For instance, not only did the 18th century French and English believe that they originated from ancient Greece but they managed to successfully 'sell' that story to modern Greeks, and later the entire world. In that sense, it is impossible not to see a parallel with China today. As it adopted the Western model in almost every respect during the course of its development, starting with accepting the communist ideology in the early stages of its westernization, and then liberal economy, and finally the Olympics, China has implicitly adopted the European identity narrative. Critics, on the other hand, fail to see the magnitude of the discrepancy that this country with such a rich tradition has made towards the West in the last several decades. To the (still living) arrogant European colonial state of mind it goes without saying that China should want to be 'like us' and accept the Olympic tradition. This same arrogance fails to ask itself if, for instance, He Kexin's Olympic gold medal in gymnastics is a victory for China or for the West.